Field efficacy of exogenously applied putrescine in wheat (Triticum aestivum) under water-stress conditions - GUPTA, SUNITA; GUPTA, N K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter (rabi) season of 2005–06 and 2006–07 taking wheat (Triticum aestivum L. emend Fiori. & Paol.) genotype ‘HD 2329’ to investigate the efficacy of putrescine under water stress condition. Putrescine (0.01, 0.1 and 1.0 mM concentrations) was applied as seed treatment, one or two foliar sprays. For water stress treatment, the number of irrigations was reduced to three as compared to six in control. Putrescine application enhanced plant height, leaf area, grain number, grain weight, grain yield and biological yield under non-stress as well as under water stress conditions. Exogenous application of 0.1 mM putrescine was found the best in most of the observations. Among mode of applications, two foliar sprays of putrescine at the time of anthesis and post anthesis performed best over seed treatment and one foliar spray of putrescine.